Pedagogical Competence of Civic Education Teachers in Senior High School: A Qualitative Analysis Based on the 2023 Teacher Competence Model - Sharla, Difa Novika; Hardoko, Aloysius; Pardosi, Jawatir; Suryaningsi, Suryaningsi (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to analyze the pedagogical competence of Civic Education teachers at MAN 2 Samarinda based on the Regulation of the Director General of Teachers and Education Personnel Number 2626/B/Hk.04.01/2023 concerning the Teacher Competency Model, focusing on creating safe learning environments, student-centered learning, and assessment practices. The research used a descriptive qualitative method through intensive classroom observations and semi-structured interviews with two teachers and six students selected purposively. Data were analyzed using the Miles and Huberman interactive model, including reduction, display, and conclusion drawing. The results indicate that teachers’ pedagogical competence is mainly concentrated at the levels of conceptual understanding and classroom-level implementation across the three aspects, but declines at higher levels such as reflection, collaboration, and professional assistance. Assessment practices represent the lowest level of achievement, as they remain largely procedural and have not functioned optimally as formative tools.